Remote Sensing for Sustainable Forest Management - Franklin, Steven E. (CRC Press, 2009)
As remote sensing data and methods have become increasingly complex and varied - and increasingly reliable - so have their uses in forest management. New algorithms have been developed in virtually every aspect of image analysis, from classification to enhancements to estimating parameters. Remote Sensing for Sustainable Forest Management reviews the literature and provides the tools for understanding and choosing remote sensing solutions for management problems.